Market dynamics of Turkish movie market (1922-1999) - Anapa, Doğan (My University, 1999)
Understanding the dynamics of Turkish movie market in a historical perspective will underline the reconsideration of micro dynamics like audience. The study gives market feedback to each related parry in the movie industry, brings into open market issues, and therefore contributes to market information sources where there isn't an organized academic study. The study also covers strenghts of American movie market along with the changing dynamics of Turkish movie market. Having implemented movie market industrilization and shifted to market globalization, American movie market has a lead role in world movie markets, and it contains a useful source of information in terms of its macro environment and marketing mix. The success of this market lies in its strenghts such as, high level of specialization and building a strong national and international distribution network which allowed for high budget and volume of motion picture production. The thesis focuses on relative impact of micro environmental and macro environmental dynamics of Turkish movie market over producers, distributors and exhibitors, along with defining the strenghts and weaknesses of changing market structures. Micro environmental factors such as, production orientation, marketing orientation, financial sources and each party's perception of audience are analysed. In addition, economical, governmental, legal, technological, international and socio-cultural factors are analysed within the macro environmental framework. u The field survey was conducted with a structured-qualitative questionairre administered to S producers, S distributors and S exhibitors by convenience sampling method, and it consists of open-ended questions
Keywords: İşletme; Pazar Analizi; Sahne ve Görüntü Sanatları; Sinema Sektörü; Türk Sineması